(untitled) (International Journal of Engineering and Computer Science, 2016)
The advent of modern technology has provided us with a platform to exchange information on a massive scale. There is always a threat of intercepting this confidential information which ultimately calls for some sort of security measure to allow uninterrupted flow of information from the sender to the receiver. Already devised methods like cryptography and steganography have been referred to as the flag bearers in this field. Cryptography is a process where a person changes the meaning of the original data by converting it into a cipher text. And steganography, on the other hand helps in hiding the cipher text or plain text in a medium thereby obscuring its existence. Both these methods are tested methods of providing security. In today’s information age, information sharing and transfer has increased exponentially. The concern around making secret information completely threat free has been a daunting problem for the experts. Cryptography combined with steganography can certainly be used to overcome this threat. The two methods of cryptography and steganography when combined help in achieving significant levels of data security thereby proving to be a better method than these processes being used as standalone ones for transmitting data over an insecure channel which is susceptible to intrusion. One of the most secure forms of steganography is Visual Steganography which is implemented commonly in image files. There might be some changes in the colour frequency of the image when the data text is embedded which would become very obvious to the person seeing it. In order to overcome the conspicuous behaviour of the image, we propose layers of data protection where the data text will first be converted to an unreadable cipher followed by embedding the cipher into an image file in an encrypted format which will then be divided into shares to achieve another layer of security. Hence, the concept of cryptography and steganography both are used to provide two layers of security followed by visual cryptography scheme to divide the image into shares for it to be transmitted over a network channel.